AB0055 Adalimumab elicits a restricted anti-idiotypic antibody response in autoimmune patients resulting in functional neutralization. (23rd January 2014) - van Schouwenburg, P.; van de Stadt, L.A.; de Jong, R.; van Buren, E.; Kruithof, S.; de Groot, E.; Hart, M.; van Ham, M.; Rispens, T.; Aarden, L.; Wolbink, G.; Wouters, D.
Abstract : Background: Worldwide millions of patients are treated with monoclonal antibodies. These biological therapeutics can be immunogenic, resulting in antibody formation which lead to loss of response. Fully human biologics such as the anti-TNFα antibody adalimumab are considered to be weakly immunogenic, but we found that the majority of Rheumatoid Arthritis patients develop anti-drug antibodies (ADA) within 28 weeks of treatment. Objectives: Here we unraveled the mechanism by which ADA lead to loss of response by investigating the full specificity of the repertoire of anti-adalimumab antibodies. Methods: The specificity of the repertoire of anti-adalimumab antibodies in a cohort of 50 ADA-positive RA patients was elucidated. In inhibition experiments using TNFa and patient derived anti-adalimumab monoclonal antibodies that were recombinantly generated after isolation of adalimumab-specific B cells. Results: The antibody response against adalimumab is highly restricted: Fab fragments of a single, monoclonal antibody specific for the idiotype of adalimumab inhibited 98.65% (25th-75th percentiles: 98.25- 99.90) of the total anti-adalimumab reactivity in sera of 50 different ADA-positive RA patients. Furthermore, we found that the anti-adalimumab response is confined to the TNFα binding region of adalimumab, thereby neutralizing its therapeutic efficacy. In line with this restricted specificity, we observed small immune complexes in the circulation of ADA-forming patients. Conclusions: The humoral immune response against adalimumab is highly restricted and limited to the idiotype of the therapeutic antibody. All antibodies result in functional neutralization of the drug, thereby providing a mechanism in which ADA formation leads to clinical non-response. Disclosure of Interest: None Declared